Tinjauan Sistematik tentang Teknologi Digital dalam Akuntansi Sektor Publik - Muslimah; Ulya, Kaela Najwa Himatul; Aji, Gunawan (Akuntansi dan Manajemen, 2025)
Digital transformation has rapidly reshaped the landscape of public sector accounting, yet a comprehensive understanding of its impact remains limited. This study aims to conduct a Systematic Literature Review (SLR) on the implementation of digital technologies in public sector accounting practices. Utilizing the PRISMA protocol, this review analyzes 25 academic articles sourced from Google Scholar, published between 2021 and 2025. Selection criteria included peer-reviewed status, topical relevance, and focus on technologies such as Artificial Intelligence, Blockchain, IoT, and e-budgeting. Findings reveal that digitalization enhances efficiency, transparency, and accountability through faster data processing and automation of internal controls. However, challenges such as digital infrastructure gaps, low digital literacy, and cybersecurity concerns persist. This study contributes by synthesizing a thematic framework outlining key trends and research gaps, offering strategic guidance for policymakers and educators in developing digitally integrated governance and curriculum models. Its practical implications include the need for human resource upskilling, robust digital auditing mechanisms, and quantitative evaluations of technology's impact on public financial management.